OPTIMIZATION OF DIAGRAMS ON USAGE OF POTENTIAL FUEL-GAS ENERGY OF CROSS-COUNTRY PIPE-LINES - A. D. Kachan; V. M. Kopko; S. A. Kachan; V. I. Kravzov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a combined power installation being a part of gas expansion set and thermal engine for gas distribution stations. It is shown that in the case when a steam turbine condensing power plant serves as a substitution station increased heating of gas prior to GES without its cooling after the set is more profitable.